Gender Equality and Sustainable Development: A Pathways Approach - Isha Ray (United Nations, 2016)
The challenges of building pathways to sustainability and enhancing gender equality are both urgent. This work explores why they must be addressed together, and how this might be done. It puts forward a ‘gendered pathways approach’, as a conceptual framework for addressing the interactions, tensions and trade-offs between different dimensions of gender equality and of sustainability. The publication provides a historical review of how diverse concepts—or narratives—about women, gender and sustainability have emerged and come to co-exist. It acknowledges tensions and trade-offs in different pathways and addresses the policy and political challenges of transforming pathways towards greater gender equality and sustainability. Ultimately, the authors argue, feminist movements and collective organizing, emerging in diverse ways and places across the world, offer the greatest hope both for challenging unsustainable pathways and for charting new ones that lead us in more sustainable, gender-equal directions.